2022
DOI: 10.18400/tekderg.902668
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrated Lime Mixing Forms and Ratios on Performance in Asphalt Pavements

Abstract: In this study; the water damage problem and indirect tensile strengths were investigated for different hydrated lime additive ratios and different hydrated lime adding methods. In this regard, many identical briquettes modified with hydrated lime have been produced. HL was used both in the bituminous binder (wet method) and as part of the filler aggregate. The hydrated lime was added in two different ways to form the defined equivalent ratios. By producing nine identical briquettes in each option, the values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A life cycle cost analysis [ 3 ] showed that HL addition saved approximately 20$ per ton on asphalt concrete, whilst increasing the expected service life of the constructed pavement by 38%. Extensive research has reported the results of the stiffening effect of HL on asphalt mixes [ 4 , 5 , 6 ] and improvement in fracture-, aging-, and moisture-resistance of asphalt concretes with HL. addition [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A life cycle cost analysis [ 3 ] showed that HL addition saved approximately 20$ per ton on asphalt concrete, whilst increasing the expected service life of the constructed pavement by 38%. Extensive research has reported the results of the stiffening effect of HL on asphalt mixes [ 4 , 5 , 6 ] and improvement in fracture-, aging-, and moisture-resistance of asphalt concretes with HL. addition [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%